1985
DOI: 10.1016/s0022-5347(17)47387-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Chlamydia Trachomatis from the Prostatic Cells in Patients Affected by Nonacute Abacterial Prostatitis

Abstract: To assess the presence of Chlamydia trachomatis in nonacute abacterial prostatitis 30 patients with urethral cultures positive for Chlamydia trachomatis underwent microbiological studies, including cultures of transrectal aspiration biopsies of the prostate. Chlamydia trachomatis was isolated from 10 of the prostatic specimens (33 per cent). In 3 cases a nonspecific cytopathogenic effect caused the destruction of the tissue cultures. Our findings demonstrate that Chlamydia trachomatis may cause ascending infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…Many organisms have been implicated has possible sources of undocumented infection, including Mycoplasma hominis, Trichomonas vaginalis, Candida species, Ureaplasma urealyticum, Chlamydia trachomatis, herpes simplex virus, and even parasites (23)(24)(25)(26)(27)(28)(29). Such an infection may actually be an inciting incident rather than an ongoing cause that leads to development of the clinical syndrome.…”
Section: Chronic Prostatitis/chronic Pelvic Pain Syndrome (Cp/cpps)mentioning
confidence: 99%
“…Many organisms have been implicated has possible sources of undocumented infection, including Mycoplasma hominis, Trichomonas vaginalis, Candida species, Ureaplasma urealyticum, Chlamydia trachomatis, herpes simplex virus, and even parasites (23)(24)(25)(26)(27)(28)(29). Such an infection may actually be an inciting incident rather than an ongoing cause that leads to development of the clinical syndrome.…”
Section: Chronic Prostatitis/chronic Pelvic Pain Syndrome (Cp/cpps)mentioning
confidence: 99%
“…These include Chlamydia trachomatis, human papillomavirus (HPV), and human herpesvirus type 8 (HHV-8) infections. C. trachomatis is a putative, candidate infection because it is intracellular and is often asymptomatic in men, which may allow it to persist in the male genitourinary tract and possibly ascend to the prostate, where it has been observed to infect prostate epithelial cells and elicit an intraprostatic inflammatory immune response (4)(5)(6). HPV and HHV-8 infections are putative candidates because they have both been associated with other cancers (cervical, vulval, anal, and penile carcinomas and Kaposi's sarcoma; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Nonbacterial prostatitis, an idiopathic disease, is the most common form of prostate inflammation constituting about 50% of all cases. There has been much speculation, but only a little proof, that chlamydial infection might be responsible for many cases of apparent nonbacterial prostatitis (19,20). However, as early as 1972, Mårdh et al showed the more frequent presence of chlamydial antibodies in men with chronic prostatitis compared with the controls (21) and later studies have also suggested that antichlamydial immunoglobulin A (IgA) and immunoglobulin G (IgG) antibodies are present in patients with chronic prostatitis (22,23).…”
Section: Introductionmentioning
confidence: 99%